2017
DOI: 10.5194/wes-2-55-2017
|View full text |Cite
|
Sign up to set email alerts
|

Blind test comparison of the performance and wake flow between two in-line wind turbines exposed to different turbulent inflow conditions

Abstract: Abstract. This is a summary of the results of the fourth blind test workshop that was held in Trondheim in October 2015. Herein, computational predictions on the performance of two in-line model wind turbines as well as the mean and turbulent wake flow are compared to experimental data measured at the wind tunnel of the Norwegian University of Science and Technology (NTNU). A detailed description of the model geometry, the wind tunnel boundary conditions and the test case specifications was published before th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
67
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 58 publications
(77 citation statements)
references
References 30 publications
4
67
0
1
Order By: Relevance
“…In this experiment T2 is controlled to its optimum power point, which strongly varies for different positions and upstream turbine operational parameters. The exact geometry and detailed performance curves of T1 are described in , while T2's characteristics can be found in Bartl and Saetran (2017). In contrast to most other turbines, the investigated model turbines rotate counterclockwise.…”
Section: Wind Turbine Modelsmentioning
confidence: 99%
“…In this experiment T2 is controlled to its optimum power point, which strongly varies for different positions and upstream turbine operational parameters. The exact geometry and detailed performance curves of T1 are described in , while T2's characteristics can be found in Bartl and Saetran (2017). In contrast to most other turbines, the investigated model turbines rotate counterclockwise.…”
Section: Wind Turbine Modelsmentioning
confidence: 99%
“…In this experiment T2 is controlled to its optimum power point, which strongly varies for different positions and upstream turbine operational parameters. The exact geometry and detailed performance curves of T1 are described in Bartl et al (2018), while T2's characteristics can be found in Bartl and Saetran (2017). In contrast to most other turbines, the investigated model turbines rotate counter-clockwise.…”
Section: Wind Turbine Modelsmentioning
confidence: 99%
“…The wind turbine model used for this study has a rotor diameter of D=0.90 m with a hub diameter of D hub =0.090 m. The tower and nacelle structure of the turbine is a slimmer re-design of the turbines used in previously used in Bartl and Saetran (2017).…”
Section: Turbine Model Inflow and Operating Conditions Turbine Modelmentioning
confidence: 99%